Answer:
[tex]f(3) = \frac{11}{2}[/tex]
[tex]f(5) = \frac{15}{2}[/tex]
[tex]f(17) =\frac{39}{2}[/tex]
Step-by-step explanation:
Given
[tex]f(n) = 3 + n - \frac{1}{2}[/tex]
Solving (a): The 3rd term
This implies that n = 3
So:
[tex]f(3) = 3 + 3 - \frac{1}{2}[/tex]
Take LCM
[tex]f(3) = \frac{6 + 6 -1}{2}[/tex]
[tex]f(3) = \frac{11}{2}[/tex]
Solving (b): The 5th term
This implies that n = 5.
So:
[tex]f(5) = 3 + 5 - \frac{1}{2}[/tex]
Take LCM
[tex]f(5) = \frac{6 + 10 - 1}{2}[/tex]
[tex]f(5) = \frac{15}{2}[/tex]
Solving (c): The 17th term
This implies that n = 17
So:
[tex]f(17) = 3 + 17 - \frac{1}{2}[/tex]
Take LCM
[tex]f(17) =\frac{6 + 34 - 1}{2}[/tex]
[tex]f(17) =\frac{39}{2}[/tex]